Design studies for stand off bomb detection - Matthew, Christopher P. (Kansas State University, 2010)
A prototype system for detecting explosives at standoff distances, using a signature based radiation scanning approach, is being developed at Kansas State University. The prototype will incorporate both a machine x-ray source and a machine neutron source to generate signatures from unknown samples of material. These signatures can be compared to templates measured or calculated from known explosive samples using a figure-of-merit. The machine neutron source uses the fusion of deuterium and tritium to create 14.1 MeV neutrons. Due to its radioactivity, the tritium must be sealed within the system. A new method of controlling the gas pressure with the DT generator was developed using a Zr-V-Fe getter supplied by a commercial firm. The shielding and collimation of the 14.1 MeV neutron source is accomplished using layers of steel, high-density polyethylene and borated high-density polyethylene. This thesis describes the development of the gas control method for the sealed neutron source, design studies for the shielding and collimation of the neutron source and modifications made to the building in which the prototype is being housed.
Keywords: Getter; 14.1 MeV neutron source; Bomb; Explosive; Detection; Vacuum pressure control; Engineering, Materials Science (0794); Engineering, Mechanical (0548); Engineering, Nuclear (0552)